Combating Important Diseases of rabi pulses by using resistant varieties - Naimuddin, Naimuddin; Mishra, Raj K; Akram, Mohd; Saabale, P R (Indian Farming, 2017)
Use of disease resistant varieties of pulses is the most cost effective and best eco-friendly method of avoiding losses caused by the diseases. In addition to the varieties listed in this article, there may be other varieties resistant to diseases which are recommended for certain states. Growers are advised to contact nearby Krishi Vigyan Kendra or Agricultural University to know in detail about the diseases resistant varieties of pulses suitable for that particular area.